KESIAPAN CALON GURU MATEMATIKA DALAM MENGHADAPI TANTANGAN ABAD 21: PERSPEKTIF PEDAGOGIS DAN INOVASI PEMBELAJARAN - Safitri, Rizka Safitri; Suparni; Sintha Sih Dewanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the pedagogical readiness and learning innovations of prospective mathematics teachers in addressing the challenges of 21st-century education. The rapid advancement of technology and digitalization requires education to incorporate 21st-century skills, including critical thinking, creativity, collaboration, and digital literacy, into the learning process. This study employs a descriptive qualitative approach, with the research participants consisting of 29 students from the Mathematics Education Program enrolled in the course "Mathematics Learning Strategies and Innovations." Data collection is conducted through the distribution of questionnaires and structured interviews to gain a comprehensive understanding of the readiness of prospective teachers. The study's findings indicate that prospective teachers possess a solid foundational understanding of pedagogical concepts but require further development in implementing innovative and adaptive teaching methods. Identified innovations in teaching include the use of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) approaches, which are seen as effective in fostering inclusive learning environments. Additionally, technologies like GeoGebra and Kahoot are utilized to enhance student interaction and engagement. Moreover, the incorporation of gamification and real-world context-based learning is viewed as crucial for boosting student motivation. These findings are expected to significantly contribute to preparing future mathematics teachers to serve as agents of change in the rapidly evolving educational landscape.